2017
DOI: 10.12669/pjms.332.12220
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral arterial blood pressure versus Central Arterial Blood Pressure Monitoring in Critically Ill Patients after Cardio-pulmonary Bypass

Abstract: Objective:To determine the accuracy of peripheral (radial) arterial access as compared to central (femoral) arterial access for measurement of invasive blood pressure (IBP) in critically ill patients after cardiopulmonary bypass.Methods:Sixty patients (60) who required high inotropic/vasopressor support on weaning from cardio-pulmonary bypass and weaned off in 2nd attempt were included in this study. The duration of this study was from June 2015 to August 2016. Radial and femoral arterial access was achieved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 25 publications
(21 reference statements)
0
2
0
Order By: Relevance
“…A minimum MAP of 70 mm Hg is recommended to mitigate hypoperfusion [ 13 ]. Nevertheless, variations in MAP have been reported among critically ill patients undergoing cardiac surgery [ 14 , 15 ], cardiopulmonary bypass [ 16 18 ], liver transplantation [ 19 , 20 ], or experiencing septic shock [ 21 , 22 ]. Notably, the administration of vasopressors is associated with an increased likelihood of clinically significant discrepancies in blood pressure measurements.…”
Section: Introductionmentioning
confidence: 99%
“…A minimum MAP of 70 mm Hg is recommended to mitigate hypoperfusion [ 13 ]. Nevertheless, variations in MAP have been reported among critically ill patients undergoing cardiac surgery [ 14 , 15 ], cardiopulmonary bypass [ 16 18 ], liver transplantation [ 19 , 20 ], or experiencing septic shock [ 21 , 22 ]. Notably, the administration of vasopressors is associated with an increased likelihood of clinically significant discrepancies in blood pressure measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies have shown variable results regarding the concordance of blood pressure readings from different arterial sites in high-risk surgical and critically ill patients. Some studies found a good correlation between these measurements, while others observed genuine differences in systolic blood pressure (SBP) and mean arterial pressure (MAP) between central and peripheral sites (6–29). This disparity has the potential to influence clinical decision-making and patient outcomes as the accuracy of invasive blood pressure monitoring is crucial in determining the stability of the circulatory system, perfusion to major organs and hence guide the need for interventions.…”
mentioning
confidence: 99%